Value Creation Through Corporate Governance - Elena Chitimus (CES Working Papers, 2013)
Companies spend time and money in order to improve their corporate governance (CG) system and also do not forget to inform third parties about their efforts in this field. CG studies the separation of power at an entity level and the segregation of responsibilities between shareholders, management, and board of directors. As a mechanism CG helps to align management's goals with those of the stakeholders in order to avoid conflict and to sustain and develop a healthy company. The objective of this article is to show how corporate governance is defined, what does it stands for and why it is important or maybe better said why companies give it so much importance.
Keywords: F23; G30; G34; M48; 330; corporate governance; overall firm performance; financial scandals; codes of conduct Romania